Genetic, Cytogenetic and Morphological Trends in the Evolution of the Rhodnius (Triatominae: Rhodniini) Trans-Andean Group (2014)
ABSTRACT: The Rhodnius Pacific group is composed of three species: Rhodnius pallescens, R. colombiensis and R. ecuadoriensis, which are considered important vectors of trypanosomes (Trypanosoma cruzi and T. rangeli) infecting humans. This group is considered as a recent trans-Andean lineage derived from the widespread distributed sister taxa R. pictipes during the later uplift of northern Andes mountain range. The widest spread species R. pallescens may be a complex of two divergent lineages with different chromosomal attributes and a particular biogeographical distribution across Central America and Colombia with several southern populations in Colombia occupying the same sylvatic habitat as its sister species R. colombiensis. Although the taxonomy of Rhodnius Pacific group has been well studied, the unresolved phylogenetic and systematic issues are the target of this paper. Here we explore the molecular phylogeography of this species group analyzing two mitochondrial (ND4 and cyt b) and one nuclear (D2 region of ribosomal 28S gene) gene sequences. The molecular analyses suggest an early divergence of the species R. ecuadoriensis and R. colombiensis, followed by a recent expansion of R. pallescens lineages. The phylogenetic relationship between sympatric R. pallescens Colombian lineage and R. colombiensis was further explored using wing morphometry, DNA genome size measurements, and by analyzing chromosomal behavior of hybrids progeny obtained from experimental crosses. Our results suggest that the diversification of the two R. pallescens lineages was mainly influenced by biogeographical events such as (i) the emergence of the Panama Isthmus, while the origin and divergence of R. colombiensis was associated with (ii) the development of particular genetic and chromosomal features that act as isolation mechanisms from its sister species R. pallescens (Colombian lineage). These findings provide new insights into the evolution of the Rhodnius Pacific group and the underlying biological processes that occurred during its divergence.